Habitats de l'âge du Bronze à Lyon-Vaise (Rhône) - Jacquet, Pierre (Documents d'archéologie française, 1998)
This volume is one of the first scientific publications devoted to the archaeological research covering Bronze Age occupation (20th-14th centuries BC) carried out during the construction of the northern ring road around the city of Lyon. It has been possible interpret the vestiges discovered as belonging to rural centresorclusters of dwellings established at a site on the Bank of the valley. The sets of objects studied, primarily ceramics, have come to constitute a valuable reference resource for the Lyon region. They testify to a composite cultural profile for the early Bronze Age. combining northern and southern characteristics, while the Bell Beaker cultural background subsists. During the late Bronze I period, however. the southern features give way to influences of the Jura and Burgundian regions and those derived from the north-western façade of the Alps. Palaeo-environmental studies conducted in conjunction with the archaeological work provide the basis for an investigation of the landscape during the Bronze Age and the foundation of the populations' subsistence economy, in keeping with the basic outlines established for the temperate regions of Western Europe.